2017
DOI: 10.15389/agrobiology.2017.3.607eng
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF THE SYMBIOTIC EFFECTIVENESS OF PEA (Pisum sativum L.) GENOTYPES IN POT EXPERIMENT

Abstract: A b s t r a c tThe successful use of plant-microbe systems based on legumes in agriculture requires creation of new cultivars of crop legumes effectively interacting with microbes. For the selection of cultivars of crop legumes, the effectiveness of interaction with beneficial soil microorganisms (EIBSM) trait has been proposed. EIBSM is estimated as a percentage of increment in a number of agriculturally important parameters (plant biomass, number and total biomass of seeds, as well as weight of 1000 seeds) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
2
6
0
1
Order By: Relevance
“…Under the conditions of this experiment, no positive effect of mycorrhiza on the growth parameters of pea during the vegetative and reproductive stages (I-V) was revealed. The data obtained here are consistent with numerous observations made by other authors who noted a low growth response of P. sativum to AMF mono-inoculation (Rivera-Becerril et al, 2002; Xavier & Germida, 2003; Borisov et al, 2004b; Desalegn et al, 2016; Zhukov et al, 2017). It was also previously shown that the effect of mycorrhiza was often not manifested under artificial lighting conditions (Konvalinková & Jansa, 2016), so it is likely that the illumination in the growth chambers used in this study was not sufficient for the growth response to occur.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Under the conditions of this experiment, no positive effect of mycorrhiza on the growth parameters of pea during the vegetative and reproductive stages (I-V) was revealed. The data obtained here are consistent with numerous observations made by other authors who noted a low growth response of P. sativum to AMF mono-inoculation (Rivera-Becerril et al, 2002; Xavier & Germida, 2003; Borisov et al, 2004b; Desalegn et al, 2016; Zhukov et al, 2017). It was also previously shown that the effect of mycorrhiza was often not manifested under artificial lighting conditions (Konvalinková & Jansa, 2016), so it is likely that the illumination in the growth chambers used in this study was not sufficient for the growth response to occur.…”
Section: Discussionsupporting
confidence: 93%
“…However, P. sativum had a relatively low growth response to mono-inoculation with AMF compared to Medicago varia , Secale cereale or Hordeum vulgare , as was demonstrated in the geographical network experiments of the All-Russia Research Institute for Agricultural Microbiology (St. Petersburg) (Yurkov et al, 2017). Furthermore, many authors have described the complete absence of an increase of pea growth parameters under conditions of mono-inoculation with AMF (Rivera-Becerril et al, 2002; Xavier & Germida, 2003; Borisov et al, 2004b; Desalegn et al, 2016; Zhukov et al, 2017). Even pea genotypes having the highest growth response to double inoculation may not show a positive response to mono-inoculation with AMF (Borisov et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this accumulation does not always result in an increase of fresh weight. The low growth response of P. sativum to AMF mono-inoculation was shown in our previous research and some other publications [ 5 , 28 , 29 , 30 ]. Precise analysis of pea plant development during AM symbiosis revealed a very important event, namely that the pea plants inoculated with AMF prolonged the active phase of the vegetation period [ 5 ].…”
Section: Discussionsupporting
confidence: 64%
“…Some pea genotypes exhibit relatively high mycorrhiza-dependence [ 26 ]. However, most of the studies conducted under model conditions [ 5 , 10 , 27 , 28 , 29 , 30 ], and in the field [ 31 ], indicate that the pea has a low responsiveness to mono-inoculation with AMF. Often, a noticeable positive effect of mycorrhization on the growth parameters of pea plants is observed only when they are grown under stressful conditions [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, involvement of high-EIBSM lines in breeding programs might increase the overall agricultural efficiency. One needs to keep in mind; however, that environmental stress, like drought, common in most pea culturing countries, might eliminate the favorable effects of symbiosis with BSM [57]. Therefore, additional experiments in adequate drought models [58] are necessary to address inoculation of high-EIBSM pea plants with BSM under conditions of environmental stress.…”
Section: Discussionmentioning
confidence: 99%